2020
DOI: 10.3892/mmr.2020.11041
|View full text |Cite
|
Sign up to set email alerts
|

Anti‑glycolipid disorder effect of epigallocatechin‑3‑gallate on high‑fat diet and STZ‑induced T2DM in mice

Abstract: epigallocatechin-3-gallate (eGcG) is beneficial for inhibiting dyslipidemia and reducing hyperlipidemic risk. The purpose of the present study was to investigate the glycolipid regulatory effects and potential mechanisms of eGcG in a high-fat diet and streptozotocin-induced type 2 diabetes mellitus (T2dM) mouse model. The results demonstrated that eGcG can decrease blood glucose levels and increase insulin resistance in T2dM mice. in addition, eGcG can regulate serum lipid levels, including those of total chol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 58 publications
1
14
0
Order By: Relevance
“…EGCG down-regulated glucose levels and up-regulated C-peptide levels in T2DM mice. 35 In summary, the current study demonstrated that EGCG modulates blood glucose in T2DM rats. Lowering blood sugar, helping maintain body mass, and reducing oxidative stress is of great significance for lipid regulation, insulin resistance, and cardiovascular protection.…”
Section: Discussionsupporting
confidence: 54%
“…EGCG down-regulated glucose levels and up-regulated C-peptide levels in T2DM mice. 35 In summary, the current study demonstrated that EGCG modulates blood glucose in T2DM rats. Lowering blood sugar, helping maintain body mass, and reducing oxidative stress is of great significance for lipid regulation, insulin resistance, and cardiovascular protection.…”
Section: Discussionsupporting
confidence: 54%
“…Generally, impaired glycolipid metabolism is a significant complication of T2DM ( 21 ), closely associated with high-calorie diets and obesity ( 22 ). Glycolipid metabolism can promote metabolic abnormalities and insulin resistance, leading to increased glucose production and defects in insulin secretion in the liver ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Substantial evidence suggests that EGCG elicit a wide range of properties, including antioxidant and antilipid deposition and anti-inflammation [141][142][143]. Extensive studies have shown that the consumption of EGCG exhibited an LDL-C reducing effect [144][145][146][147]. A systematic review found that EGCG could significantly decrease the plasma LDL-C level at doses between 107 and 856 mg/d [148][149][150].…”
Section: Flavan-3-olsmentioning
confidence: 99%